Simulation of nitrogen and phosphorus pollution in typical agricultural and forested basins as well as relevant reduction effect based on SWAT model - Wu Li; Chen Zhe; Liu Hui-ying; Wang Dun-qiu (Water Supply, 2021)
Non-point source nitrogen and phosphorus pollution is a critical threat to aquatic ecosystems and a potential risk to drinking water safety. To precisely control nitrogen and phosphorus pollution in the river basin, in this study, we identified key pollution areas of the river basin, analyzed the main characteristics of pollution sources as well as their contribution to the river basin pollution, and conducted simulation analysis on reduction measures based on the SWAT model. The results showed the following. (1) The simulation effect of the calibrated model was good, and sub-basins 3, 39 and 96 were the key source areas, the main sources of pollution were combined pollution from livestock and poultry breeding and planting industry. (2) Crops had the largest input and output for both nitrogen and phosphorus, the output of which was 6,137.8 t/a and 562.4 t/a respectively. The urban point sources had the highest output rates of nitrogen and phosphorus, 75.7% and 67.5% respectively. (3) With the optimal combination of reduction measures, nitrogen and phosphorus were reduced by 1,438.9 t and 85.3 t respectively, i.e., the reduction rates were the highest. The reduction effect for total nitrogen was better than that for total phosphorus. HIGHLIGHTS Using local census data of pollution sources based on SWAT model.; Identifying the key pollution sources through the characteristics of main pollution source and output.; Using data of pollution sources examining contribution rate and output rate.; The reduction effects of different reduction measures were compared.; Using long-term hydrology, water quality data rate and validation, the result of model is reliable.;